Chemical Analysis of Some Cosmetics, Detergent and Pharmaceutical Minerals used in Traditional Medicine of Iran - Mashkouri Najafi, Nahid; Mohammad Bagheri, Azadeh; Ghasemi, Ensieh; Alizadeh, Reza (Asian Journal of Chemistry, 2010)
In this study, some minerals, which are used in pharmaceutical, detergent and cosmetic products in traditional medicine of Iran, have been analyzed with the aim of identification and determination of their components for toxic element contents. The typical samples with their trademark such as detergent minerals "Gele Sarshoye", cosmetic minerals "Sefidab Roye, Sefidab Ghale, Sefidab Hamam, Kafe Darya and Sorme (Kohl)" and pharmaceutical minerals "Gele Armani, Shangarf, Booreh Armani and Mordar Sang" were collected from traditional drug stores in Iran for sample testing. The qualitative and quantitative analyses were carried out using X-ray diffraction, X-ray fluorescence, inductively coupled plasma optical emission spectroscopy, inductively coupled plasma mass spectroscopy and atomic absorption spectro-scopy techniques. Due to lack of control and standardization these minerals have presented positive traces of toxic elements and clear differences when comparing the chemical analysis of similar products.